2003
DOI: 10.1093/ndt/18.2.310
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adults with end-stage renal disease since childhood is only partially impaired

Abstract: Dialysis patients with paediatric ESRD have an impaired physical quality of life, but in contrast to dialysis patients with adult ESRD onset, they have a normal mental quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 18 publications
8
21
2
3
Order By: Relevance
“…We found that dialysis patients with paediatric ESRD had an impaired physical QoL as adults, but they had a normal mental QoL. Important medical determinants of QoL were co-morbidity for all patients and disabilities for patients that had received a transplant [1]. Rosenkranz et al [2] found that general and health-related satisfaction with life of adult patients with ESRD was reduced compared to that of the general population.…”
Section: Introductionmentioning
confidence: 78%
“…We found that dialysis patients with paediatric ESRD had an impaired physical QoL as adults, but they had a normal mental QoL. Important medical determinants of QoL were co-morbidity for all patients and disabilities for patients that had received a transplant [1]. Rosenkranz et al [2] found that general and health-related satisfaction with life of adult patients with ESRD was reduced compared to that of the general population.…”
Section: Introductionmentioning
confidence: 78%
“…1 Correlation between child-self and parent-proxy total scores in chronic kidney disease (CKD) (r=0.612, p=0.000) Fig. 2 Correlation between child-self and parent-proxy total scores in dialysis patients (DP) (r=0.519, p=0.005) children with end-stage renal disease (ESRD) to prepare them for active participation in society in adult life [20,21]. In contrast to research on QoL in adults, few studies on children and adolescents in the general population have been carried out using large representative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Little is yet known about the factors influencing the extent to which child-self and parent-proxy reports differ with respect to QoL. Concordance rates between child and parent varied between different clinical groups and healthy children as well [21,26]. In some studies, children evaluated themselves more negatively than did their parents [26,27], whereas other parent-proxy reports had lower QoL scores than did child-self assessments [12,14,26,28,29].…”
Section: 00mentioning
confidence: 99%
“…End-stage renal disease in childhood is associated with retarded development of social as well as cognitive capacities (4,31). Dialysis leads to prolonged parental dependency into adult age, unemployment and a lower level of education, relative to the duration of dialysis (1,12,32). The development of confidence and independency in adolescence is better in patients transplanted without prior dialysis (33,34).…”
Section: Discussionmentioning
confidence: 99%